Temporal Application of the New Romanian Civil Code Provisions Concerning Engagement - CIOCOIU, Mariana (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
Engagement is a marital, mutual promise subject to the fundamental conditions required for marriage conclusion and is a mandatory phase before marriage. The New Romanian Civil Code brings a series new stipulations that specifically protect family among which the chapter dedicated to the institution of engagement is a novelty in what Romanian law is concerned. From a sociologic and economic point of view engagement can be considered an event that parallels the religious ceremony in importance. Engagement expresses the same covenant, feelings, and emotions, is officiated in a holy place and forgoes marriage. In the modern sense of the term, promises of marriage are backed by the future spouses cohabitation. The paper tackles the question of engagement in the light of the new stipulations of the new Romanian Civil Code.